Ergonomic Standard Compliance of Nurses in Tertiary Hospitals in Edo State, Nigeria - Obaseki, C.; Erhabor, N. I. (NIU Journal of Social Sciences; Vol 9 No 4 (2023): NIU Journal of Social Sciences, Vol. 9 No. 4, December 2023DO - 10.58709/niujss.v9i4.1778, 2023)
Healthcare professionals are responsible for many people’s lives. In their daily routines, they care for a number of people and have a lasting impact on patients. Nursing can take a toll on the body and one way to mitigate long-term bodily damage is through an ergonomic friendly work environment. There are many work-related dangers that nurses face on a daily basis. Thus the study assessed the compliance of nurses towards the ergonomics standard in University of Benin Teaching Hospital UBTH, Nigeria. A descriptive survey research design was used in the study. The study population was all nurses in University of Benin Teaching Hospital and the sample size for the study was One hundred and fifty five (155) respondents selected across ten departments in the tertiary health center. The purposive sampling technique was used to select the participants in the study.  After obtaining the informed consent from the subjects, compliance level was assessed by using ergonomic task analysis scale by observation method.  The result of the study showed that the subjects had low compliance on the ergonomic standards of healthcare workers (nurses). Also various ergonomic-based risk factors are associated with their work process including awkward postures, high repetition and excessive work durations which are of great concern in this case. Several engineering and administrative-based controls were offered which would help to eliminate/reduce the presence of the ergonomic-based risk factors, improve their compliance to ergonomic standards and thus lower the potential of developing WMSDs among nurses. Keywords: Ergonomics, Nurses, Safety and task analysis